2020
DOI: 10.1093/ptj/pzaa181
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Physical Therapist Intervention Is Associated With Mobility Status and Disposition at Hospital Discharge for Patients With COVID-19

Abstract: Objective For patients diagnosed with the novel coronavirus, COVID-19, evidence is needed to understand the effect of treatment by physical therapists in the acute hospital on patient outcomes. The primary aims of this study were to examine the relationship of physical therapy visit frequency and duration in the hospital with patients’ mobility status at discharge and probability of discharging home. Methods This retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 51 publications
2
58
0
1
Order By: Relevance
“…This is especially important for older adults who are at the greatest risk for complications and mortality if they contract COVID‐19 3,4 . Rehabilitation providers contribute uniquely to interdisciplinary discharge planning by providing critical evaluation of a patient's functional abilities and rehabilitation prognosis in the context of the individual's medical complexity, hospital course, psychosocial factors, and environmental features (i.e., home set‐up) 5,6 . The COVID‐19 pandemic has retained these elements as critical to discharge planning 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This is especially important for older adults who are at the greatest risk for complications and mortality if they contract COVID‐19 3,4 . Rehabilitation providers contribute uniquely to interdisciplinary discharge planning by providing critical evaluation of a patient's functional abilities and rehabilitation prognosis in the context of the individual's medical complexity, hospital course, psychosocial factors, and environmental features (i.e., home set‐up) 5,6 . The COVID‐19 pandemic has retained these elements as critical to discharge planning 7 .…”
Section: Introductionmentioning
confidence: 99%
“…To date, several groups have approached the problem regarding the creation of a dedicated team in order to better manage the high number of pronations in critically ill COVID-19 patients (Cotton et al, 2020;Doussot et al, 2020;Johnson et al, 2021;Ng et al, 2020;Short et al, 2020). However, no studies reported data concerning the impact of a physiotherapy team on the incidence of pronation-induced complications.…”
Section: Discussionmentioning
confidence: 99%
“…The studies published in September 2020 were conducted in the following World Health Organization regions: 16 in Europe (Italy [4][5][6][7][8][9][10][11][12] , United Kingdom [13][14][15] , Belgium 16 , Germany 17 , Switzerland 18 , and Netherlands and Belgium together 19 ), 14 in the Americas (11 in the United States of America (USA) [27][28][29][30][31][32][33][34][35][36][37] , 2 in Brazil 38,39 and 1 in Canada 40 ), 6 in Western Pacific (China 20 -21 , Japan 22 , Republic of Korea 23 ,Singapore 24 , Australia 25 ), and one in the South-East Asia region (India 26 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…COPYRIGHT© EDIZIONI MINERVA MEDICA historical cohort 5,7,16,26,31,32,35 ), whereas the remainder 8 papers (21.6%) were Level 3 (4 cohort 9,13,14,22 and 4 cross sectional studies 10,19,33,37 ) (Table I). No RCT or QRCT were found.…”
Section: Evidence Level Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation